Aplikasi Pengarsipan Data Administrasi Mahasiswa Pada Program Studi Teknik Informatika Berbasis Website - Mutiara (Lembaga Pengembangan Kinerja Dosen, 2024)
The Archiving System application is an important tool to support the management of information and administration given the rapid development of technology (gadgets) today, for this reason research and development of Archiving applications with a case study of the Andi Djemma University Palopo Informatics Study Program. The method used in this research is a method that produces new products from the results of the research itself, namely R&D or research and development with the RAD development model. The results of this study found that: Website-based Student Administration Data Archiving Application of Informatics Engineering Study Program in its manufacture using Visual Studio and in the software development process using the RAD method and in its design using UML, In this study produced an application that is able to provide convenience for students and the Study Program in accessing and presenting archiving information, This application has been running stably, and is easily understood by students as evidenced by the results of a questionnaire distributed by the author to respondents who scored 83% based on the conversion table this application is categorized as very feasible.